Μ‐Opioid agonists for preventing emergence agitation under sevoflurane anesthesia in children: a meta‐analysis of randomized controlled trials. Issue 2 (28th November 2015) - Tan, Yuan; Shi, Yisa; Ding, Hui; Kong, Xiangbin; Zhou, Haijiao; Tian, Jinhui
Summary: Background: Emergence agitation (EA) is an adverse effect after sevoflurane anesthesia in pediatric patients. The effectiveness of prophylactic μ ‐opioid agonists fentanyl, remifentanil, sufentanil, and alfentanil in preventing EA is debatable. Methods: A literature search was conducted to identify clinical trials that observed the effect of μ ‐opioid agonists fentanyl, remifentanil, sufentanil, and alfentanil on preventing EA in pediatric patients under sevoflurane anesthesia. The statistical software RevMan 5.3 was used for meta‐analysis. Data from each study were combined using the relative ratio (RR), weighted mean differences, and their associated 95% confidence intervals. I 2 was used to evaluate heterogeneity. Subgroup analysis was conducted to investigate the possible influences of patient age, adenotonsillectomy, premedication, N2 O, propofol, and regional block/local anesthetics on preventing EA with prophylactic administration of μ ‐opioid agonists. Publication bias was checked using funnel plots and Begg's test. Results: This meta‐analysis showed the inclusion of 19 randomized controlled trials with 1528 patients (857 patients received μ ‐opioid agonists therapy and 671 patients had placebo). The pooled data indicated that prophylactic μ ‐opioid agonists fentanyl, remifentanil, sufentanil, and alfentanil significantly decreased the incidence of EA [RR = 0.49 (0.38, 0.64), I 2  = 42%, P  = 0.04; RR = 0.57 (0.33, 0.99), I 2  = 37%, P  = 0.19; RR = 0.18 (0.08, 0.39), I 2  = 0%, P  = 0.98; and RR = 0.56 (0.40, 0.78), I 2  = 6%, P  = 0.34, respectively]. All subgroup analyses strengthened the proof for lower incidence of EA under sevoflurane anesthesia after fentanyl administration. A possibility of publication bias was detected in the fentanyl group. Conclusions: This meta‐analysis suggested that prophylactic μ ‐opioid agonists fentanyl, remifentanil, sufentanil, and alfentanil could significantly decrease the incidence of EA under sevoflurane anesthesia in children compared to placebo. Considering the limitations of the included studies, more clinical studies are required.